The arts of Shinto - Kageyama, Haruki (Weartherhill, 1973)
Shinto, the 'Way of the Gods', is the religion of Japan preceding the arrival of Buddhism from Korea during the 6th century AD. Central to Shinto beliefs are the ''kami,'' animistic gods perceived in all aspects of nature. This book, documenting a unique major exhibition from Japan, begins with a wide-ranging intro. to Shinto which traces its role in Japanese culture. Each of its 5 sections opens with an authoritative essay from an international scholar. Includes: masks, ceramics, mirrors, bells, sculpture, paintings, lacquer, ceremonial clothing, swords & armor. Some are National Treasures, rarely removed from their shrines, & many have never before been seen outside Japan. They offer a fascinating insight into the sacred art of ancient Japan. 100s of color illustrations